A Fresh View on the Outer Space Treaty (Studies in Space Policy,, 2018)
On the occasion of the 50th anniversary of the Outer Space Treaty this book gives a first insight into where the next generation considers room for further improvement of the Outer Space Treaty in order to cope with upcoming aspects such as providing solutions for the emerging commercial, economic, environmental and social questions. At the time of the adoption of the Outer Space Treaty in 1967 the purpose of this treaty was to avoid conflicting military situations in space. However, 50 years later the Outer Space Treaty is n demand to meet the ever increasing space activities and the different actors involved such as the rise of the private sector players.